Enhancing the academic curricula: content management systems and digital collections functioning together? - Vrana, Radovan (Array, 2005)
Purpose of this poster is to discuss role of course management system (CMS - software packages supporting students’ learning) and support they can provide in the process implementation of new academic curricula at the Croatian universities. Poster will also try to reflect on possibility of linking external electronic content to the course management system as a mode of significant content enhancement necessary for the advancement of the teaching process at the Croatian universities already relying on more extensive use of electronic information resources in general. The teaching process at the Croatian universities relies more and more on support of course management systems, software which enables interactive teaching process during which student becomes independent learner. The success of this type of teaching is depending on many factors, among which are user interface, online help, user profile, various user interaction tools such as chat, forum, or instant messaging, testing and grading student’ s work, but also on well developed content creation possibilities, and finally, on the quality of content system presents to its users. Content creation part of any course management system is important because it has direct influence on the quality of interaction and use of the course management system or equivalent software that can support communication between user and digital content users need for various purposes. Existing content creation modules of the course management systems should contain several key elements such as: HTML editor, support for different file formats for import into the CMS, backup system for already created content, possibility of creating a comment on certain part of content by student, support for more than one type for upload of content into the course management system etc. More extensive list of features can be found at http://www.carnet.hr/referalni/obrazovni/oca/usporedba (in Croatian) or http://www.carnet.hr/referalni/obrazovni/en/oca/method (in English). Based on the list of features, individuals and institutions are choosing among available course management system packages. The other side of the user – digital content relationship is electronic information resources in general and digital collections in particular. As the number of digital collections accessible on the Internet is increasing, it is expected that general interest for this type of information resources will also increase, especially in teaching and research. Both activities are deeply rooted at universities, and can be carried out partially of fully with a help of some course management system or other software equivalent. What course management systems usually lack is support for inclusion of digital objects from digital collections directly into the course management systems not just in form of URLs, but as content that can be integrated and displayed (presented) within the course management system. This is a feature which would add additional quality to the on-line learning. To achieve this, both course management systems and digital collections should support some type of commonly recognized mechanism for content linking, and use. Both, creators of course management systems and developers of digital collections should cooperate more extensively on that issue. For instance, many projects of digital collection development were initiated in academic community however during the early stages of their development ; sometimes they were closed for wider public who wished to explore their content. Today, the situation is quite different, digital collections are more accessible not only to the members of academic community worldwide, but also to the general public, and development of hardware and software is making access to the digital collections quality content easier. These are some of the reasons for the growth of interest in digital collections. Development of course management systems has also shown great improvement. Today we have both commercial and open source software solutions that can fully support teaching at universities. An example of an open source course management system is Moodle (http://www.moodle.org), used at the Faculty of Philosophy in Zagreb (http://www.ffzg.hr/omega). Generally speaking, course management systems such as Moodle are very useful in teaching, and can greatly improve teaching, while still having limited set of features. It remains to be seen what the future of its development will bring, having in mind that better content creation module and a mechanism for integration of digital content are still needed. What we also shouldn't forget is that digital libraries and digital collections are constantly being developed offering new and improved tools for access to content in digital collections, thus becoming competition to the course management systems. While seeking solution for better integration of digital collection content into course management systems, digital collection developers should take into account certain organizational aspect of digital collection development which manifest themselves in four dimensions:[1] • Physical proximity and social restrictions on using the system • Level of compatibility of files in different systems • The possibility of integrating the system into a person or group's work • Availability of training and help to users. These four dimensions (and other that may emerge) should be considered when choosing digital collections for use in teaching and, and when choosing course management system package which will offer possibility of integration of their content into system's modules. As new academic curricula at the Croatian universities require quality support for the teaching process, features and quality of the requests will become more and more important. It will also be important to promote use of quality electronic information resources among students and researchers at the Croatian universities, especially if they will be available in the Croatian language. [1] Xie, Hong ; Wolfram, Dietmar. State digital library usability: contributing organizational factors. // Journal of the American society for information science and technology, 53, 13(2002), 1086. Xie, Hong ; Wolfram, Dietmar. State digital library usability: contributing organizational factors. // Journal of the American society for information science and technology, 53, 13(2002), 1085-1097.